Oslo Manual on Select Topics of the Law of Armed Conflict Rules and Commentary - Dinstein, Yoram (Springer Nature, 2020)
This new open access book provides a valuable restatement of the current law of armed conflict regarding hostilities in a diverse range of contexts: outer space, cyber operations, remote and autonomous weapons, undersea systems and devices, submarine cables, civilians participating in unmanned operations, military objectives by nature, civilian airliners, destruction of property, surrender, search and rescue, humanitarian assistance, cultural property, the natural environment, and more. The book was prepared by a group of experts after consultation with a number of key governments. It is intended to offer guidance for practitioners (mainly commanding officers); facilitate training at military colleges; and inform both instructors and graduate students of international law on the current state of the law.